A murine model of tuberculosis/type 2 diabetes comorbidity for investigating the microbiome, metabolome and associated immune parameters. Issue 2 (23rd March 2021) - Sathkumara, Harindra D.; Eaton, Janet L.; Field, Matt A.; Govan, Brenda L.; Ketheesan, Natkunam; Kupz, Andreas
Abstract: Tuberculosis (TB) is one of the deadliest infectious diseases in the world. The metabolic disease type 2 diabetes (T2D) significantly increases the risk of developing active TB. Effective new TB vaccine candidates and novel therapeutic interventions are required to meet the challenges of global TB eradication. Recent evidence suggests that the microbiota plays a significant role in how the host responds to infection, injury and neoplastic changes. Animal models that closely reflect human physiology are crucial in assessing new treatments and to decipher the underlying immunological defects responsible for increased TB susceptibility in comorbid patients. In this study, using a diet‐induced murine T2D model that reflects the etiopathogenesis of clinical T2D and increased TB susceptibility, we investigated how the intestinal microbiota may impact the development of T2D, and how the gut microbial composition changes following a very low‐dose aerosol infection with Mycobacterium tuberculosis ( Mtb ). Our data revealed a substantial intestinal microbiota dysbiosis in T2D mice compared to non‐diabetic animals. The observed differences were comparable to previous clinical reports in TB patients, in which it was shown that Mtb infection causes rapid loss of microbial diversity. Furthermore, diversity index and principle component analyses demonstrated distinct clustering of Mtb ‐infected non‐diabetic mice vs. Mtb ‐infected T2D mice. Our findings support a broad applicability of T2D mice as a tractable small animal model for studying distinct immune parameters, microbiota and the immune‐metabolome of TB/T2D comorbidity. This model may also enable answers to be found to critical outstanding questions about targeted interventions of the gut microbiota and the gut‐lung axis. Abstract : EDD‐feeding leads to the development of cardinal features of clinical T2D. T2D causes substantial dysbiosis in gut microbiota. Mtb infection significantly decreases gut microbial diversity. Clinically relevant model to study immune, metabolome and microbiota‐related parameters in TB/T2D comorbidity.